Impact of Poly(ADP-Ribose) Polymerase (PARP) and Immune Checkpoint Inhibitor Combinations on the Viability of Triple-Negative Breast Cancer Cells - Tusha Sharma; Kumaraswamy Naidu Chitrala (Proceedings)
Background: Breast cancer is one of the most common cancer types and the second most frequent one among women in the United States [...]